Experimental study on permeability stress sensitivity in tight sandstone oil reservoirs - Xiaofeng Tian,; Linsong Cheng,; Wenqi Zhao,; Yiqun Yan,; Xiaohui He,; Qiang Guo, (Universiti Kebangsaan Malaysia, 2015)
In this paper, seven permeability stress sensitivity experiments were conducted to show the features of permeability stress sensitivity. The cores in the experiments were taken from the tight sandstone oil reservoir in Ordos Basin. Then advanced technologies, such as casting thin section, scanning electron microscope and rate-controlled mercury penetration, were applied to explain the mechanism of permeability stress sensitivity in tight oil reservoirs. The results indicated that the permeability reduction and recovery in gas permeability stress sensitivity increases as the permeability decreases. This was resulted from the maximal throat radius. The permeability reduction in liquid permeability stress sensitivity increases at first and then decreases as the permeability decreases. The permeability recovery decreases to zero as the permeability decreases. Additionally, the differences between gas and liquid permeability stress sensitivity become greater as the permeability decreases. These were resulted from the effect of the critical throat radius. This paper corrects the mistakes about the stress sensitivity in tight oil reservoirs from gas permeability stress sensitivity experiments which is significant to the development of tight sandstone oil reservoirs.